Comparison of primary health care services between urban and rural settings after the introduction of the first urban health centre in Vyronas, Greece. - Mariolis, Anargiros; Mihas, Constantinos; Alevizos, Alevizos; Mariolis-Sapsakos, Theodoros; Marayiannis, Konstantinos; Papathanasiou, Marek; Gizlis, Vassilios; Karanasios, Dimitris; Merkouris, Bodossakis (BMC Health Serv Res, 2008)
BACKGROUND: Discrepancies in primary health care (PHC) services between urban and rural settings have already been studied in many countries; however, limited information exists regarding countries, such as Greece, where public Health Centres dedicated to primary care have not been in existence in major cities. The objective of this study was to evaluate points of divergence or convergence between an urban and a rural health centre, in an attempt to underline challenges faced by the introduction of urban health centres in Greece. METHODS: A cross-sectional analysis was conducted in the Health Centre of Vyronas, Athens, Greece and in the Health Centre of Nea (New) Madytos, Thessaloniki Prefecture, Greece between February 2004 and February 2006. The profile of the population seeking care, as well as data on the services provided were collected and compared. In addition, the reason for choosing each primary health care unit was also recorded. RESULTS: More patients visited the urban centre (145415 vs. 112513), while the pattern of services utilized by the citizens differed significantly (p < 0.001) between the two Health Centres. The frequency of diagnoses made according to ICPC-2 was not similar in the two Health Centres (p < 0.001). The three most frequent reasons for the adults choosing the Health Centre for their problem were low waiting time, proximity to residence and satisfaction with the services provided in previous visits in Vyronas. CONCLUSION: The results of this study highlight the significant differences regarding PHC services utilization between an urban and a rural population. Urban citizens seem to have different health needs and reasons for choosing a PHC unit than residents of the Greek countryside. Proximity to health services and the public character of the urban health centre seem to be its main advantages.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Choice Behavior; Community Health Centers; Cross-Sectional Studies; Diagnosis-Related Groups; Greece; Health Services Accessibility; Humans; Infant; Middle Aged; Patient Acceptance of Health Care; Primary Health Care; Rural Health Services; Socioeconomic Factors; Urban Health Services; Utilization Review; Workforce